Analisis Pelaksanaan Standar Pendidik Dan Tenaga Kependidikan Di SDN 2 Sukamaju (Penelitian di SDN 2 Sukamaju Tasikmalaya) - Aryana Dinoor Putra; Cece Rakhmat; Febri Fajar Pratama (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The standards for educators and education staff are standards that regulate the qualifications that must be possessed by educators and education staff, both academic and non-academic qualifications. the standards of educators and educational staff at SDN 2 Sukamaju still do not meet the standards in accordance with PP No. 57 of 2021 Article 20 paragraph 1 and Article 23 paragraph 1. Therefore this research was conducted to find out the educational standards contained in SDN 2 Sukamaju based on some indicator. The research method used is a qualitative method with a SWOT analysis which is divided into Strengths, Weaknesses, Opportunities, Threats. The results show that educators and education staff at SDN 2 Sukamaju have met the standards of educators and education staff, but at the point of recruiting teaching staff there are a few obstacles where these obstacles are caused by the education moratorium, more precisely as stated in the Tasik City Regional Regulation No. 4 of 2007 concerning the Implementation of Education, so that there is a need for adjustments.